(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The study confirms the observation that “smokers drink and drinkers smoke". In this study, we aim to assess the relationship between nicotine addiction and the severity of affective disorders in hospital patients with alcohol dependence. The study involved 105 inpatient patients diagnosed with alcohol dependence. They were provided with SCID-I, AUDIT, Fagerstrom test for nicotine addiction, Hamilton Depression and Anxiety assessment scale. The results showed that the average severity of affective disorders was high in patients with alcohol dependence and nicotine addiction, but there was no significant difference between nicotine-dependent and independent groups in the severity of affective disorders. Comparative studies between smoking patients with alcohol dependence and various smoking or non-smoking groups with affective disorders can provide valuable information.